(3GdMOGFb GdfGXQI aj CMcGe GdYJQI GdWGgQIs - (3GdOQGRj GdHMQGf, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s ((3MSjf Hf Ydj GdcYHjs)
(3ChdgG (B:s
(3ef JMQje GdSaQ YOe JMQjeg hcdeG COi hLhOg Edi YOeg agh HGWd CeG GdedGReI aEfg dG ebJVi dJMQje GdSaQ EdG GdGSJdRGe dahGJ GdLeYI ceG gh GdeaQhV heJi MQe GdSaQ JSbW GdLeYI ceG JbOe adG jMQe (B...s
(3BNQgG (B:s
..(3aGFOI jSJMH LHQ GdebUhQGJ HGdJSHjMGJ GdCQHY GdeTghQI aj OHQgG deG QhGg SdjeGf Hf MaU GdeQhRj bGd (B: (3bGd Gdabjg GdYScQj Y jLH Ydi GdeSGaQ Cf jbhd aj OHQ cd UdGI jbUQ ajgG (B... (3gPG BNQ GdcdGes
(3Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8/215s
(3GdPQjYI (B6/208 (1557)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis